2022
DOI: 10.1371/journal.pone.0262320
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of vaccination timeliness and associated factors among children in Toke Kutaye district, central Ethiopia: A Mixed study

Abstract: Introduction Age inappropriate vaccination of children increases the rate of mortality and morbidity. All studies conducted in some areas of Ethiopia were only quantitative in nature and focused on the main cities ignoring rural communities. Objective The objective of this study is to assess vaccination timeliness and associated factors among children in Toke Kutaye district, central Ethiopia. Methods A community-based cross-sectional study with quantitative and qualitative data collection methods was used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
16
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 20 publications
(30 reference statements)
7
16
2
Order By: Relevance
“…In this study, giving birth at a health facility was also significantly associated with vaccine timelines. This finding is supported by studies conducted in Ethiopia by analyzing EDHS data (36) and Kutaye district (28), which revealed that if the mother delivers the child at a health facility, it increases the timely initiation of vaccination at the recommended interval. This is because mothers who delivers the child in a health facility had a greater opportunity of being advised about the benefits of EPI services and getting health education (28).…”
Section: Discussionsupporting
confidence: 57%
See 4 more Smart Citations
“…In this study, giving birth at a health facility was also significantly associated with vaccine timelines. This finding is supported by studies conducted in Ethiopia by analyzing EDHS data (36) and Kutaye district (28), which revealed that if the mother delivers the child at a health facility, it increases the timely initiation of vaccination at the recommended interval. This is because mothers who delivers the child in a health facility had a greater opportunity of being advised about the benefits of EPI services and getting health education (28).…”
Section: Discussionsupporting
confidence: 57%
“…Moreover, having sufficient knowledge about vaccination increases the odds of vaccinating the child at the recommended schedule. Similarly, studies done in the northeast Ethiopia (21) and central Ethiopia (28)showed that insufficient knowledge about vaccination increased the delay in vaccinating at the recommended interval. The possible explanation is that knowledge lessens the likelihood of having negative feelings about childhood vaccination, which increases practice and timeliness.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations